Association of objective visual impairment with suicidal ideation and suicide attempts among adults aged ≥50 years in low/middle-income countries. Issue 11 (30th April 2021) - Smith, Lee; Shin, Jae Il; Barnett, Yvonne; Allen, Peter M; Lindsay, Rosie; Pizzol, Damiano; Jacob, Louis; Oh, Hans; Yang, Lin; Tully, Mark A; Veronese, Nicola; Koyanagi, Ai
Abstract : Background: There is currently limited literature on the association between visual impairment and suicidal thoughts and behaviours, especially among older adults from low/middle-income countries (LMICs). Thus, we aimed to investigate the associations of objectively measured distance visual impairment with suicidal ideation and suicide attempts among adults aged ≥50 years from six LMICs and to identify potential mediators. Methods: Cross-sectional, community-based, nationally representative data from the WHO Study on global AGEing and adult health were analysed. Objective distance visual acuity was measured using the tumbling E logMAR chart, and vision impairment was categorised as none, mild, moderate and severe. Self-reported information on past 12-month suicidal ideation and suicide attempts was also collected. Multivariable logistic regression and mediation analysis were conducted. Results: Data on 34 129 individuals aged ≥50 years (mean (SD) age, 62.4 (16.0) years; 47.9% men) were analysed. After adjustment for potential confounders, compared with no visual impairment, severe visual impairment was significantly associated with suicidal ideation (OR=9.50; 95% CI=2.47 to 36.52). Moderate and severe visual impairment were significantly associated with a 2.22 (95% CI=1.14 to 4.35) and 11.50 (95% CI=1.44 to 91.88) times higher odds of suicide attempts, respectively. Disability, poor self-rated health, mobility and loneliness explained 14.0%, 9.3%, 7.2% and 6.3% of the association between moderate/severe visual impairment and suicide attempts, respectively. Conclusion: Interventions to reduce suicidal ideation and suicide attempts among older adults with visual impairment in LMICs are required, targeting identified mediators, while using tested strategies for suicide prevention per se in LMICs may yield beneficial outcomes.